PRELIMINARY RESEARCH OF APIONIDAE AND NANOPHYIDAE (COLEOPTERA: CURCULIONOIDEA) OF THE BIOSPHERE RESERVE GOLIJA-STUDENICA (Acta Entomologica Serbica, 2010)
Golija-Studenica are given. The identification of 192 adult specimens collected during August 2008 confirmed the presence of 34 species (32 from the family Apionidae and two from Nanophyidae). The taxonomy and all collecting details are presented here (date of collecting, localities, type of habitat, plants, numbers of females, males and total number of specimens).